2019
DOI: 10.1111/ppa.13097
|View full text |Cite
|
Sign up to set email alerts
|

Size does matter – susceptibility of apple for grey mould is affected by cell size

Abstract: Apple is a seasonal product that is stored for long periods of time, during which fungal‐caused decay can occur. Previous infection experiments of intact Jonagored apple with Botrytis cinerea displayed apparent differences in lesion expansion rate with respect to inoculation position on the fruit (on, above or below the equator). The goal of this study was to investigate whether these differences are consistent or not and if so, to relate them to fruit characteristics. The study involved measuring the hue angl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Their results showed that in the incompatible interaction, the phenylpropanoid pathway was upregulated faster and stronger. Furthermore, previous research of us has found a link between cell density and resistance in apple, possibly due to a correlation with biosynthetic capacity; meaning, fruit with a higher cell density may be able to mount a larger defense response in a given time ( Naets et al, 2019 ). All this evidence indicates timing and magnitude of defense responses plays a key role in effective defense, and that, in the case of apple- B. cinerea , there is an important role for the MVA pathway.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Their results showed that in the incompatible interaction, the phenylpropanoid pathway was upregulated faster and stronger. Furthermore, previous research of us has found a link between cell density and resistance in apple, possibly due to a correlation with biosynthetic capacity; meaning, fruit with a higher cell density may be able to mount a larger defense response in a given time ( Naets et al, 2019 ). All this evidence indicates timing and magnitude of defense responses plays a key role in effective defense, and that, in the case of apple- B. cinerea , there is an important role for the MVA pathway.…”
Section: Discussionmentioning
confidence: 92%
“…This method had been shown to give reproducible infections. The side of the fruit was arbitrary, but important to fix, because previous research of us showed that the side of the fruit could have an effect on susceptibility to B. cinerea ( Naets et al, 2019 ). Each wound was inoculated with either 2 μL of the spore suspension (which will be denoted as B. cinerea inoculated) or 12 g L –1 PDB (mock inoculated).…”
Section: Methodsmentioning
confidence: 99%
“…In particular, EF, which relates to shelf life and market price, is a significant index. Fruit firmness is an illustration of a complex quantitative attribute impacted by genes that regulate cell wall, cell dilatation, and stratum trait [ 53 , 54 , 55 ]. In a study by Moreno et al [ 11 ], five QTLs ( FF2.2 , FF3.5 , FF8.2 , FF8.4 , and FF10.2 ) related to flesh firmness were detected using PI 161375 (SC) and Piel de Sapo (PS).…”
Section: Discussionmentioning
confidence: 99%